2017
DOI: 10.1016/j.combustflame.2016.02.026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygenated fuel properties on diesel spray combustion and soot formation

Abstract: Diesel engines have advantages due to their potential for high fuel conversion efficiency. However, it is necessary to reduce pollutant emissions, particularly NOx and soot to meet emission mandates. Many studies have shown that oxygenated fuel additives can effectively reduce soot emissions. In this research, to investigate the effect of oxygenated fuel properties on combustion and soot emission, CFD simulations were carried out using newly developed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 28 publications
(33 reference statements)
2
37
0
Order By: Relevance
“…Therefore, its combustion is almost soot free, even at stoichiometric air/fuel conditions. 10 This enables a drastic reduction of nitrous oxides (NO X ) emissions, as significantly increased exhaust gas recirculation (EGR) rates are possible without disadvantages in soot emissions. Nonetheless, most of the previous studies only investigated the use of DME in conventional Diesel engines, which were not or only to a minor degree modified.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, its combustion is almost soot free, even at stoichiometric air/fuel conditions. 10 This enables a drastic reduction of nitrous oxides (NO X ) emissions, as significantly increased exhaust gas recirculation (EGR) rates are possible without disadvantages in soot emissions. Nonetheless, most of the previous studies only investigated the use of DME in conventional Diesel engines, which were not or only to a minor degree modified.…”
Section: Introductionmentioning
confidence: 99%
“…Also, multi-zone models have been used for examining the influence of diesel/biofuel blending ratio and molecular structure on CI engine performance and emissions [20]. Finally, comprehensive CFD models have been used for assessing the impact of oxygenated fuel properties on diesel spray combustion and soot formation [21]. The influence of fuels chemical composition and properties on CI engine transient operational and environmental performance has been examined in the past using detailed simulations models [22].…”
Section: Introductionmentioning
confidence: 99%
“…3 Computational fluid dynamics (CFD) simulations have also been used to study the chemical mechanism of DME, and the results showed that because DME molecules have oxygen atoms and there is no direct connection of C-C bonds, it can achieve smokeless combustion. 4 Based on its lower emissions, the researches of DME were mainly focused on the alternative fuels for internal combustion engines. Ji et al 5 added DME to the spark-ignited ethanol engine and the results showed that the thermal efficiency increased and the flame development and propagation durations were shortened with the increase of DME fraction.…”
Section: Introductionmentioning
confidence: 99%